2019
DOI: 10.1038/s41391-019-0167-9
|View full text |Cite
|
Sign up to set email alerts
|

Decipher identifies men with otherwise clinically favorable-intermediate risk disease who may not be good candidates for active surveillance

Abstract: Background We aimed to validate Decipher to predict adverse pathology (AP) at radical prostatectomy (RP) in men with National Comprehensive Cancer Network (NCCN) favorable-intermediate risk (F-IR) prostate cancer (PCa), and to better select FIR candidates for active surveillance (AS). Methods In all, 647 patients diagnosed with NCCN very low/low risk (VL/LR) or FIR prostate cancer were identified from a multi-institutional PCa biopsy database; all underwent RP with complete postoperative clinicopathological in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(26 citation statements)
references
References 37 publications
0
24
0
2
Order By: Relevance
“…In this cohort, the Decipher score was an independent predictor of adverse pathology, i.e., high-grade and/or high-stage at prostatectomy, (OR 1.34 per 0.1 unit increase, 95% CI 1.11-1.63). 13 Similarly, Kim and colleagues analyzed Decipher scores from the biopsies of 266 patients with NCCN very-low, low-, and favorable-intermediate-risk prostate cancer and also reported that the Decipher score was an independent predictor of adverse pathology on prostatectomy (odds ratio 1.29 per 10% increase, 95% CI 1.03-1.61 per 0.1 unit increase). 25 However, by directly evaluating outcomes of patients actually on active surveillance, we identified a significant association of Decipher test results and tumor upgrading.…”
Section: Discussionmentioning
confidence: 99%
“…In this cohort, the Decipher score was an independent predictor of adverse pathology, i.e., high-grade and/or high-stage at prostatectomy, (OR 1.34 per 0.1 unit increase, 95% CI 1.11-1.63). 13 Similarly, Kim and colleagues analyzed Decipher scores from the biopsies of 266 patients with NCCN very-low, low-, and favorable-intermediate-risk prostate cancer and also reported that the Decipher score was an independent predictor of adverse pathology on prostatectomy (odds ratio 1.29 per 10% increase, 95% CI 1.03-1.61 per 0.1 unit increase). 25 However, by directly evaluating outcomes of patients actually on active surveillance, we identified a significant association of Decipher test results and tumor upgrading.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al [ 83 ] and Herleman et al [ 84 ] evaluated the ability of Decipher© to predict adverse pathology in patients with NCCN favourable-intermediate risk PCa who undergone a RP at first treatment. Decipher was an independent predictor of adverse pathology and adding Decipher improved the CAPRA score.…”
Section: Tissue Biomarkermentioning
confidence: 99%
“…This test incorporates 22 coding and non-coding genes that cover seven cancer pathways, including angiogenesis, invasion and metastasis, or growth and differentiation [50]. It generates a score ranging from 0 to 1, with higher values indicating an increased probability for both AP and poorer oncologic outcomes [52].…”
Section: Tissue Biomarkersmentioning
confidence: 99%